2009
DOI: 10.1016/j.biortech.2008.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Biodrying for mechanical–biological treatment of wastes: A review of process science and engineering

Abstract: Biodrying is a variation of aerobic decomposition, used within mechanical-biological treatment (MBT) plants to dry and partially stabilise residual municipal waste. Biodrying MBT plants can produce a high quality solid recovered fuel (SRF), high in biomass content. Here, process objectives, operating principles, reactor designs, parameters for process monitoring and control, and their effect on biodried output quality are critically examined. Within the biodrying reactors, waste is dried by air convection, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
128
0
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(148 citation statements)
references
References 54 publications
(101 reference statements)
3
128
0
17
Order By: Relevance
“…This method is different than other works of biodrying because they uses an external airflow to drag moisture (Sugni et al 2005;Navaee-Ardeh et al 2006;Zhang et al 2008;Zhang et al 2009;Velis et al 2009; NavaeeArdeh 2010).…”
Section: Fig 6: Data and Graphs From Three Greenhouses In The Fourthmentioning
confidence: 98%
See 1 more Smart Citation
“…This method is different than other works of biodrying because they uses an external airflow to drag moisture (Sugni et al 2005;Navaee-Ardeh et al 2006;Zhang et al 2008;Zhang et al 2009;Velis et al 2009; NavaeeArdeh 2010).…”
Section: Fig 6: Data and Graphs From Three Greenhouses In The Fourthmentioning
confidence: 98%
“…In this work, part of the water in the waste was evaporated, levels of moisture in waste below 15% being reached in some cases. In their works, Velis et al (2009) reported that commercial process cycles are completed within 7-15 days, with mostly loses of water 25-30% w/w, leading to moisture contents of <20% w/w.…”
Section: Fig 6: Data and Graphs From Three Greenhouses In The Fourthmentioning
confidence: 99%
“…Zhang [16,17] improved the moisture and accelerated the decomposition of waste with high moisture content by increasing the circulating leachate during hydrolytic degradation prior to aerobic decomposition. There were a few studies in aerobic rotary bio-drying reactor of MSW [2,12,14,15]. Khajon [5] reported that combined hydrolytic-aerobic in rotary bio-drying process could produce homogeneous RDF from MSW.…”
Section: Introductionmentioning
confidence: 99%
“…Drying technology reduces the moisture content of a matrix by the application of heat, and produces dried outputs of desired characteristics (Velis et al, 2009). However, thermal dryers using external energy have been used for sludge dewatering, which do not rely on microbial produced heat, leading to high costs (Kurt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Biodrying, an alternative way to treat biomass waste, is an economical and energy-saving method that removes water from waste material using the microbial heat originating from organic matter degradation, which is based on a process similar to composting (Winkler et al, 2013). The moisture reduction during biodrying is as follows: water molecules evaporate from the SSBM surface into the air, after which the evaporated water is transported and removed by airflow (Velis et al, 2009). The main biodrying mechanism is convective evaporation, which utilizes heat produced from the biodegradation of organic matter and is facilitated by mechanically controlled aeration (NavaeeArdeh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%